2020
DOI: 10.1038/s41598-020-61720-w
|View full text |Cite
|
Sign up to set email alerts
|

Severe maternal morbidity by mode of delivery in women with twin pregnancy and planned vaginal delivery

Abstract: Planned vaginal delivery in twin pregnancies has three potential outcomes: vaginal or cesarean delivery of both twins, or cesarean for the second twin. Our objective was to assess the association between delivery mode and severe acute maternal morbidity (SAMM) in women with twin pregnancies and planned vaginal deliveries. We limited this planned secondary analysis of the JUMODA cohort, a national prospective population-based study of twin deliveries, to women with planned vaginal delivery at or after 24 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Moreover, Madar et al [ 20 ] recently found that one fifth of the association between twin pregnancy and severe maternal outcomes may be mediated by caesarean delivery, yet caesarean rate was also high for single births in our sample. Recent findings from a French study verified that caesarean for the second twin and for both twins had higher risk of severe maternal morbidity compared to vaginal delivery for both twins [ 39 ], which also emphasizes the importance of reducing caesarean rates for twins in Brazil.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, Madar et al [ 20 ] recently found that one fifth of the association between twin pregnancy and severe maternal outcomes may be mediated by caesarean delivery, yet caesarean rate was also high for single births in our sample. Recent findings from a French study verified that caesarean for the second twin and for both twins had higher risk of severe maternal morbidity compared to vaginal delivery for both twins [ 39 ], which also emphasizes the importance of reducing caesarean rates for twins in Brazil.…”
Section: Discussionmentioning
confidence: 91%
“…are guided by a pragmatic view about cervical ripening, such as all large prospective observational studies in obstetrics [30][31][32][33]. These studies allow multiple analyses of data and conclusions about pragmatic management and consequences of some current obstetric conditions that were not adapted to randomized controlled trials (i.e., twins with The JUmeaux MODe d'Accouchement (JUMODA) study) [30,[34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The greater risk for mothers undergoing an unplanned CS must be kept in mind when counselling women on the mode of birth with twin pregnancies. The literature reports higher risks of short-term complications in mothers undergoing unplanned secondary CS compared to planned primary CS and vaginal delivery mainly due to higher anaesthesia- and surgery-related morbidity [ 24 – 26 ]. The results of our research, however, confirm that vaginal birth for monochorionic twins ≥36 weeks of gestation is just as safe as for women with DC-DA pregnancies.…”
Section: Discussionmentioning
confidence: 99%